Life history traits that predispose South African linefishes to overexploitation - Haupt, Meghan (Department of Biological Sciences, 2019)
Globally, the status of many fish stocks remains unknown, of which the majority fall under data-limited small-scale fisheries. Management decisions in most of these fisheries are difficult due conflicting objectives and views from fisheries managers and scientists. In South Africa, the traditional boat-based ‘linefishery’ provides such an example of a small-scale, multi-species fishery with a long history. The historical de facto open access nature of this fishery resulted in continuous declines in catches of many linefish species, and in 2000 the fishery was declared to be in a state of emergency. This led to a reduction of up to 70% within the fishery, among other measures, such as introductions of size and bag limits. Assessing the status of linefish species is difficult due to a lack of reliable long-term data for the majority of species. The aims of this study were therefore: (1) to quantify the stock status for all linefish species with available life history and size composition information, (2) compare current and historical stock levels to ascertain if the reduction in effort facilitated any recovery in linefish species and (3) correlate the current stock status estimates to life history traits to identify simple indicators of resilience to exploitation. For this purpose, length frequency data from 1988-1990 and 2008-2010 and biological parameters sourced from literature were used to conduct per-recruit analysis to estimate spawner biomass depletion (SBD) for both time periods. The majority of the 26 species analyzed, (68%) showed improvements in spawner biomass between the two time periods, with 12 species undergoing a change in stock status (i.e. improving from collapsed or overexploited). Specifically, increases in length-at-capture (Lc) as well decreases in fishing mortality (F) facilitated recovery for many species. Asymptotic length (L∞), as well as the ratio between Lc / L∞ and Lc / Lopt (where Lopt is the optimum length) were found to be significantly correlated to spawner biomass depletion. Kruskal Wallis analyses revealed that only movement pattern had a significant relationship to SBD, more specifically, migratory species were significantly more depleted than resident ones. This study identifies simple indicators that, in the absence of conventional stock assessments, provide fisheries managers with a fundamental understanding of a species’ susceptibility to overexploitation – offering another decision making tool for use in data poor fisheries such as the South African linefishery.